Serological and Traditional Detection of Sarcocystis Species Isolated from Human and Beef Meat in Diyala Province - Enas Nazar Abood; Haleem Hamza Hussain Al- Zubaidei (Diyala Journal for Veterinary Sciences, 2025)
Sarcocystis is a protozoan, intracellular parasitic disease of the phylum Apicomplexa, it is important disease in Asia, especially the western regions of the continent. It is considered one of the important zoonotic diseases, the infection wide geographic spreading caused by various species. The total Infection rate of traditional methods was 65 % (65 100) of sarcocysts isolated from esophagus of 100 cattle were slaughtered at Diyala slaughter house during the period from November 2023 to May 2024. Cattle age ranged from (2-5) years. Different traditional techniques were made to detected sarcocystosis, peptic digestion technique was highly sensitive technique 100% according all other traditional methods. Then Trichnoscopy were 30(30%) while the squeezing less sensitive 26(26%) respectively. The majority of male animals recorded higher infection incidence 75% while the female’s cattle rate was 53,8 from the total exanimated animals. The result showed that the highest infection rate was recorded in animal of old age above 4-year-old 100% with significant differences between the age groups. the bradyzoites of Sarcocystis parasite were seen by examining the sediment of the digested muscle fluid as banana shape with a spik end of front and rounded rear end and slightly clear nucleus positioned toward the rear end, measurements 13.2× 2.8 μm. In human the total ELISA results of the blood samples (male and female) showed total infected rate (15.28%). the male recorded highly infection rate in 10(34.48%) while the lowest rate in female was (6.34% (The infection rate according to male ages groups showed that (15-25) age highly infected (20.68%) .In females, the highest infection rate recorded in (25-35) age group than other groups.in conclusion the sarcocystis infection in cattle meat and human serum were elevated in Diyala areas and it has become more effected on the health of society due to the consumption of imported or under cocked meat. Therefore, more studies must be conducted to determine the propagate of the disease and attempt control it distribution.